2008
DOI: 10.1556/jep.6.2008.4.2
|View full text |Cite
|
Sign up to set email alerts
|

The encryption theory of humor: A knowledge-based mechanism of honest signaling

Abstract: Abstract. We propose that intentionally produced humor is a form of communication that evolved to broadcast information about the self and to obtain information about others by honestly signaling the fact of shared common knowledge. According to this model, humorous utterances and acts are encrypted in the sense that what makes the joke funny is not merely its surface content, but a relationship between the surface content and one or more unstated implicatures which are known by both the sender and the receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 18 publications
(12 reference statements)
2
59
0
7
Order By: Relevance
“…If spontaneous laughter originated from a highly conserved play signaling system shared by our closest primate relatives (e.g., the sound of labored breathing during physical play) (Provine, 2000), honest displays might function to guide adaptive behavior in receivers in the form of trust and cooperation. Several functions for human laughter have been proposed such as signaling playful and cooperative intent (Gervais & Wilson, 2005;Mehu & Dunbar, 2008), implicit preferences (Lynch, 2011), encrypted knowledge (Flamson & Barrett, 2008;Flamson & Bryant, 2013) or group coalitions (Bryant, 2012). Dishonest signals associated with communicative behaviors of affiliative intent could facilitate manipulative strategies, and we should expect vigilance that minimizes their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…If spontaneous laughter originated from a highly conserved play signaling system shared by our closest primate relatives (e.g., the sound of labored breathing during physical play) (Provine, 2000), honest displays might function to guide adaptive behavior in receivers in the form of trust and cooperation. Several functions for human laughter have been proposed such as signaling playful and cooperative intent (Gervais & Wilson, 2005;Mehu & Dunbar, 2008), implicit preferences (Lynch, 2011), encrypted knowledge (Flamson & Barrett, 2008;Flamson & Bryant, 2013) or group coalitions (Bryant, 2012). Dishonest signals associated with communicative behaviors of affiliative intent could facilitate manipulative strategies, and we should expect vigilance that minimizes their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Judging someone's attractiveness from something as brief as a personal advertisement may mean raters rely more on humour style to garner information about personality, though this corresponds more broadly with the sexual selection theory of humour (MILLER 2000) and the Encryption Model of humour (FLAMSON and BARRETT 2008). Producing humour requires many important cognitive skills, such as theory of mind, abstract thinking, and highly advanced language skills (POLEMINI and REISS 2006), common knowledge and problem-solving abilities (FLAMSON and BARRETT 2008), as well as creativity and intelligence (GREENGROSS and MILLER 2011), therefore producing humour is potentially an honest signal and a shortcut to demonstrating these valuable traits. The current study has shown that a humorous partner can be attractive to both men and women, perhaps for different reasons, but that the style of humour used is important as it communicates different personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, there has been growing interest in the ultimate functions of laughter and humor. Laughter and humor may play a number of different (not always mutually exclusive) roles in human communication, including expediting courtship, facilitating the flow of an interaction/conversation, synchronizing emotional states, and social bonding (Bachorowski and Owren 2001;Bressler et al 2006;Cowan and Little 2012;Curry and Dunbar 2013;Dunbar et al 2012;Flamson and Barrett 2008;Gervais and Wilson 2005;Grammer 1990;Grammer and Eibl-Eibesfeldt 1990;Hurley et al 2011;Li et al 2009;Mehu and Dunbar 2008;Owren and Bachorowski 2003). However, the underlying cognitive mechanisms that both enable these effects to work and determine the maximum complexity of jokes are much less well understood.…”
Section: Introductionmentioning
confidence: 99%